Development of Product Quality Control Instruments Student Learning Results in Practice Courses Wood Work at Universitas Negeri Padang - Yunesvi, Putri Amarta; Prima, Fani Keprila (Universitas Negeri Padang, 2024)
The product of student learning outcomes in wood working practice courses currently does not have an instrument to determine its quality control. This is based on the discovery of several defects in the products of student learning outcomes in the Wood Work Practice course at the Department of Civil Engineering, Universitas Negeri Padang. This study aims to develop a quality control instrument on student learning products in wood working practice courses and find out how much validity the quality control instrument for student learning products in wood working practice courses. The research was conducted at the Department of Civil Engineering, Universitas Negeri Padang. The type of research used is Research and Development (research and development) or abbreviated as R & D. This is a type of research used to produce certain products, and test the effectiveness of the product. The research stages include (1) Decide, (2) Design, (3) Development, (4) Evaluate. The data collection technique used a questionnaire filled out by expert lecturers of the Wood Work Practice course. The resulting data is processed using the Microsoft Excel application to determine the validity of the product. The result of this research is a guidebook for filling in wooden furniture Quality Control instruments with a validity percentage of 87% so that the product is declared valid and suitable for use.